Testing association between LRRK2 and Parkinson's disease and investigating linkage disequilibrium. Issue 2 (7th February 2006) - Paisán-Ruíz, C; Evans, E W; Jain, S; Xiromerisiou, G; Gibbs, J R; Eerola, J; Gourbali, V; Hellström, O; Duckworth, J; Papadimitriou, A; Tienari, P J; Hadjigeorgiou, G M; et al.
Abstract : Background: We and others recently identified the gene underlying PARK8 linked Parkinson's disease (PD). This gene, LRRK2, contains mutations that cause an autosomal dominant PD, including a mutation, G2019S, which is the most common PD causing mutation identified to date. Common genetic variability in genes that contain PD causing mutations has previously been implicated as a risk factor for typical sporadic disease. Methods: We undertook a case-control association analysis of LRRK2 in two independent European PD cohorts using 31 tagging single nucleotide polymorphisms (tSNPs) and five potentially functional SNPs. To assess the structure of this locus in different populations, we have performed linkage disequilibrium (LD) analysis using these variants in a human diversity panel. Results: We show that common genetic variability in LRRK2 is not associated with risk for PD in the European populations studied here. We also show inter-population variability in the strength of LD across this locus. Conclusions: To our knowledge this is the first comprehensive analysis of common variability within LRRK2 as a risk factor for PD.